2022
DOI: 10.1590/2177-6709.27.6.e2221285.oar
|View full text |Cite
|
Sign up to set email alerts
|

Association between atypical swallowing and malocclusions: a systematic review

Abstract: Objective: This systematic review aims to answer the following focus question: “Is there an association between atypical swallowing and malocclusions?”. Methods: Appropriate word combinations were chosen and tailored specifically for each of the following electronic databases: EMBASE, Latin American and Caribbean Literature in Health Sciences (LILACS), LIVIVO, PubMed/Medline, Scopus, Web of Science, and gray literature, without any restrictions, up to February 2021. According to the selection criteria, only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
(92 reference statements)
0
0
0
Order By: Relevance
“…In fact, a recent systematic review indicated an association between atypical swallow and malocclusions. 43 Assaf et al 3 in a sample of 547 children observed that open bite, deep bite, and posterior crossbite were associated with altered lingual posture. Thus, the results of the present study could explain the possible alteration in lingual kinetics in patients with DD.…”
Section: Discussionmentioning
confidence: 98%
“…In fact, a recent systematic review indicated an association between atypical swallow and malocclusions. 43 Assaf et al 3 in a sample of 547 children observed that open bite, deep bite, and posterior crossbite were associated with altered lingual posture. Thus, the results of the present study could explain the possible alteration in lingual kinetics in patients with DD.…”
Section: Discussionmentioning
confidence: 98%
“…A physiological swallowing process depends on the function and posture of the tongue. Atypical or incorrect lingual postures are consistently linked to facial deformities in children with deciduous and mixed dentition [18].…”
Section: Swallowingmentioning
confidence: 99%